2014
DOI: 10.1364/josab.31.000526
|View full text |Cite
|
Sign up to set email alerts
|

Simplified bond-hyperpolarizability model of second harmonic generation, group theory, and Neumann’s principle

Abstract: We discuss the susceptibility third-rank tensor for second harmonic and sumfrequency generation, associated with low index surfaces of silicon (Si(001), Si(011) and Si(111)) from two different approaches: the Simplified Bond-Hyperpolarizablility Model (SBHM) and Group Theory (GT). We show that SBHM agrees very well with the experimental results for simple surfaces because the definitions of the bond vectors implicitly include the geometry of the crystal and therefore the symmetry group. However, for more compl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(19 citation statements)
references
References 19 publications
0
19
0
Order By: Relevance
“…The main difference is that for the Si bulk two neighboring tetrahedral elements are required to model the response of the complete conventional cell whereas only one tetrahedral is required to describe the surface. Therefore, the point group for this surface is C 2v , as we have discussed in our previous work [16]. Based on this, we can contract the general EFISH tensor in Eq.…”
Section: Efish Represented By a Third Rank Tensormentioning
confidence: 93%
See 2 more Smart Citations
“…The main difference is that for the Si bulk two neighboring tetrahedral elements are required to model the response of the complete conventional cell whereas only one tetrahedral is required to describe the surface. Therefore, the point group for this surface is C 2v , as we have discussed in our previous work [16]. Based on this, we can contract the general EFISH tensor in Eq.…”
Section: Efish Represented By a Third Rank Tensormentioning
confidence: 93%
“…[18,19] is defined in this way and their representation changes when the sample is rotated. Therefore we apply the following bond definition [16]:…”
Section: Sbhm Analysis Of Thg and Efishmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, it can also be inferred from the location of the nonzero elements that all the tensors are symmetric. In other words, they obey the Kleinman symmetry [14]:…”
Section: Fcc and Bcc Surface Responsementioning
confidence: 99%
“…Another important step towards the understanding of SHG in diamond and zincblende lattices was the investigation of the third-rank susceptibility tensor that was obtained from the simplified bond-hyperpolarizability model (SBHM) and group theory (GT) [14,15], where it was shown that one can derive from GT the SBHM tensor. e work was later extended to show that the model can fit electric-field-induced second-harmonic (EFISH) experimental results in metal-Oxide semiconductor (MOS) with good accuracy [16].…”
Section: Introductionmentioning
confidence: 99%